Waveform Characteristics of Tunnel Blast Waves and a Wave-Blocking Method - Xianshun Zhou; Xuemin Zhang; Tianhe Ren; Xuefeng Ou; Wenchao Xiong; Liming Zhang; Lei Zhang (Shock and Vibration)
The impact of blast wave air overpressure (AOp) may cause damage to nearby structures and significant noise pollution. In order to minimize the impact of the blast wave on the buildings around the tunnel, a new wave-blocking trolley (NWBT) was proposed to control the AOp during the construction of the Baitacun tunnel, as the nearby villages were located less than 100 m from the tunnel portal. In the study, the characteristics of the blast wave pressure profiles were studied by field measurements and numerical simulations and the Friedlander equation parameters were obtained. Second, the controlling effect and working mechanism of the NWBT were verified to be effective. The measured peak AOp was weakened from 2.49 kPa to 0.55 kPa with the operating NWBT, which meets the requirements of Chinese specifications. Furthermore, a numerical simulation for the impact process of the NWBT was established using the ANSYS/LS-DYNA software. Finally, it was found that a shorter distance from the NWBT to the source of the blast makes a better contribution to its wave-blocking effect. The waveform characteristics obtained in the study contribute to the design of tunnel surrounding structures; the application of the NWBT is a successful wave-blocking method for tunnels adjacent to environmentally sensitive areas.